Socio-Political Unrest in Pakistan: A Perception of University Students in the Province of Balochistan, Pakistan - Junaid Aman; Muhammad Babar Akram; Muhammad Saud (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2018)
Pakistan has been suffering from issues of socio-political, economic and provincialism despite having a democratic federal form of government. The issue of provincialism has made Balochistan one of the volatile places regarding social unrest and instability. Therefore the present study was conducted to know the perspective of youth regarding social unrest in Balochistan. Questionnaire used as a survey instrument for data collection. Population of the study was students studying in various universities of Balochistan. A sample of 200 respondents was selected randomly from three universities of Quetta a province of Balochistan. Majority of the respondents agreed that economic deprivation, security issues, federal dominancy over Balochistan province and lack of political will on the part of local politicians were the major reasons. According to the studies suggested that this province has large amount of minerals reserves and whole country is getting benefits from it, whereas on the other side the present study concluded that lack of access to basic public facilities further aggravates the already volatile security situation in the province due to nationalistic feelings among youth. A few suggested measures are providing more educational opportunities, provision of justice and state willingness to exert proper governance, law and order.